Capacitation promotes a shift in energy metabolism in murine sperm - Tourmente, Maximiliano; Sansegundo, Ester; Rial, Eduardo; Roldan, Eduardo R. S. (Frontiers in Cell and Developmental Biology, 2022)
In mammals, sperm acquire fertilization ability after a series of physiological and biochemical changes, collectively known as capacitation, that occur inside the female reproductive tract. In addition to other requirements, sperm bioenergetic metabolism has been identified as a fundamental component in the acquisition of capacitation. Mammalian sperm produce ATP through two main metabolic processes, oxidative phosphorylation (OXPHOS) and aerobic glycolysis that are localized to two different flagellar compartments, the midpiece, and the principal piece, respectively. In mouse sperm, the occurrence of many events associated with capacitation relies on the activity of these two energy-producing pathways, leading to the hypothesis that some of these events may impose changes in sperm energetic demands. In the present study, we used extracellular flux analysis to evaluate changes in glycolytic and respiratory parameters of murine sperm that occur as a consequence of capacitation. Furthermore, we examined whether these variations affect sperm ATP sustainability. Our results show that capacitation promotes a shift in the usage ratio of the two main metabolic pathways, from oxidative to glycolytic. However, this metabolic rewiring does not seem to affect the rate at which the sperm consume ATP. We conclude that the probable function of the metabolic switch is to increase the ATP supply in the distal flagellar regions, thus sustaining the energetic demands that arise from capacitation.